The Physical and administrative obstacles to the use of teachers in basic and secondary education in Karak governorate for e-learning - Al-Dmour, Rowaydah Faiq Hammad (Journal of Educational and Psychological Sciences, 2020)
The study aimed at uncovering the physical and administrative obstacles faced by female teachers in their use of e-learning in the basic and secondary education stages in the governorate of Karak. In order to achieve the objectives of the study, the researcher used the descriptive method. The study tool consisted of a questionnaire that was distributed to a sample of 150 teachers representing 25% of the study population. Using the statistical program (spss) (3.96). At the level of the two axes, the axis of administrative obstacles obtained an average of 4.12 and the physical obstacles at an average of 3.79 and all of them were high. The results showed that there were no statistically significant differences between the basic school , And secondary school in physical constraints, while there are differences of statistical significance Primary schools, secondary schools in administrative and macro-level constraints, and for basic schools. In the light of the results, a number of recommendations and proposals were presented to overcome the obstacles facing the use of e-learning in Karak and all the Kingdom.